Experiences of returning to campus in the COVID-19 pandemic among administrative faculty staff: a job demands and resources approach - Majeke, Vika (Organisational Psychology, 2025)
The purpose of this study was to explore and develop deep understanding of return to campus experiences of administrative faculty staff- from their remote working to in person working conditions at a South African university. Administrative faculty staff play a crucial role in service delivery of the university, however, their return to campus following COVID-19 was layered with psychological and emotional experiences. A phenomenological focus group study with 11 administrative faculty staff was conducted. Thematic analysis on the focus group data revealed key themes: (1) Remote work as shaping return-to-work; (2) We don't have much choice or voice”: decision-making as one-sided and (3): Long-haul covid: returning to work as a ‘different' person.